Long-term treatment with rilzabrutinib in patients with immune thrombocytopenia - Kuter, David J; Mayer, Jiri; Efraim, Merlin; Bogdanov, Lachezar H; Baker, Ross; Kaplan, Zane; Garg, Mamta; Trněný, Marek; Choi, Philip Y; Jansen, A J Gerard; McDonald, Vickie; Bird, Robert; et al. (Blood advances, 2024)
Immune thrombocytopenia (ITP) is an autoimmune disease associated with autoantibody-mediated platelet destruction and impaired platelet production, resulting in thrombocytopenia and a predisposition to bleeding. The ongoing, global phase 1/2 study showed that rilzabrutinib, a Bruton tyrosine kinase inhibitor specifically developed to treat autoimmune disorders, could be an efficacious and well-tolerated treatment for ITP. Clinical activity, durability of response, and safety were evaluated in 16 responding patients who continued rilzabrutinib 400 mg twice daily in the long-term extension (LTE) study. At LTE entry, the median platelet count was 87 × 109/L in all patients, 68 × 109/L in those who had rilzabrutinib monotherapy (n = 5), and 156 × 109/L in patients who received concomitant ITP medication (thrombopoietin-receptor agonists and/or corticosteroids, n = 11). At a median duration of treatment of 478 days (range, 303-764), 11 of 16 patients (69%) continued to receive rilzabrutinib. A platelet count of ≥50 × 109/L was reported in 93% of patients for more than half of their monthly visits. The median percentage of LTE weeks with platelet counts ≥30 × 109/L and ≥50 × 109/L was 100% and 88%, respectively. Five patients discontinued concomitant ITP therapy and maintained median platelet counts of 106 × 109/L at 3 to 6 months after stopping concomitant ITP therapy. Adverse events related to treatment were grade 1 or 2 and transient, with no bleeding, thrombotic, or serious adverse events. With continued rilzabrutinib treatment in the LTE, platelet responses were durable and stable over time with no new safety signals. This trial is registered at www.clinicaltrials.gov as #NCT03395210 and www.clinicaltrialsregister.eu as EudraCT 2017-004012-19.
Keywords: výsledek terapie; trombocytopenie; Purpura, Thrombocytopenic, Idiopathic; Hemorrhage; thrombopoetin; idiopatická trombocytopenická purpura; receptory Fc; krvácení; Thrombopoietin; Humans; Thrombocytopenia; Receptors, Fc; Treatment Outcome; lidé